Information Literacy Instruction in Engineering Graduate Courses: Instructional Design and Reflection - Shiyi Xie; Eric Savory (Issues in Science and Technology Librarianship)
Prior research on information literacy instruction in engineering graduate programs rarely considers course instructor perspectives, and instead only uses student feedback to evaluate the efficacy of information literacy instruction. This study documents the authors’ efforts to evolve the library curriculum to motivate student learning and meet the course needs. Data collected from the student survey and course instructor questionnaire found that most students reported that the instruction was engaging and satisfying, but evaluations of the usefulness of the instruction were mixed. The course instructor was satisfied with the students’ overall work in information gathering though found their project reports unsatisfactory in terms of report writing and critical thinking. The findings shed light on student needs and faculty expectations of engineering project-based graduate courses.